Causality among selected oils and fats prices - Mohd. Arshad, Fatimah; A. Ghaffar, Roslan (PORIM, 1988)
This paper aims at ascertaining the casual relationship in particular the lead-lag relationship between selected fats and oils prices. The study utilises cross-correlation technique suggested by Haugh (1972, 1976) and Pierce (1977), which is essentially looking at the relationship between the estimated innovations of stationary time series. The lead-lag relationship and inference on the direction of causality between the prices are tested using U statistic. The study shows that there exists an instantaneous relationship between the selected fats and oils price. While soyabean prices are shown as apparently leading other seedoils like groundnut and sunflower oils and tallow there is a feedback causality between soyabean prices and palm oil prices.